Muslim marriage, divorce and custody of children in the State of Perak / Jamilah Mohd Din - Mohd Din, Jamilah (Faculty of Law, 1985)
The main purpose of this project paper will deal with discussion on marriage, divorce, custody of infant and matrimonial relief available to Muslim women. The law governing the Muslim marriage, divorce and custody of children in Perak which has been validatedly by constitution (Amendment) in September 1984, coupled with subsidiary legislation that is "Undang-undang Nikah Cerai Rujuk 11/1 965 which laid down the various rules and procedures of marriage and divorce. In Perak, unlike other states, it consists 16 district altogether which are subjected under the same Enactment. The districts ares- 1. Ipoh 2. Batu Gajah 3. Parit 4. Kampung Gajah 5. Teluk Intan 6. Lumut 7. Tapah 8. Slim River 9. Ku al a Kangsar 10. Taiping 11. Bagan Serai